2009
DOI: 10.2119/molmed.2008.00109
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Serum Macrophage Migration Inhibitory Factor (MIF) Concentrations in Chronic Kidney Disease (CKD) Are Associated with Markers of Oxidative Stress and Endothelial Activation

Abstract: Chronic kidney disease (CKD) carries an increased risk of cardiovascular disease (CVD). Macrophage migration inhibiting factor (MIF) is a proinflammatory cytokine implicated in the pathogenesis of sepsis, autoimmune disease, atherogenesis, and plaque instability, and is a known cardiac depressant. This post-hoc, cross-sectional study examined whether MIF serum concentrations are elevated in CKD patients. Our study included CKD 3-5 patients with moderate to severe renal dysfunction (n = 257) (mean age SD; 55 ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
26
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 26 publications
3
26
0
3
Order By: Relevance
“…The association between MIF and autoimmune kidney disease was further investigated by Bruchfeld et al, who studied 257 patients with chronic kidney disease different etiologies. They suggested that high MIF levels in these patients are closely linked to endothelial activation and that MIF might play a role in the vascular disease associated with chronic kidney disease [39]. …”
Section: Mif In Autoimmune Diseasesmentioning
confidence: 99%
“…The association between MIF and autoimmune kidney disease was further investigated by Bruchfeld et al, who studied 257 patients with chronic kidney disease different etiologies. They suggested that high MIF levels in these patients are closely linked to endothelial activation and that MIF might play a role in the vascular disease associated with chronic kidney disease [39]. …”
Section: Mif In Autoimmune Diseasesmentioning
confidence: 99%
“…The proinflammatory cytokine macrophage migration inhibitory factor (MIF) is associated with inflammatory nephritis, kidney transplant rejection, and chronic kidney dysfunction . Recently, Payen et al reported that MIF is increased in septic patients who developed AKI within 48 hours after intensive care unit admission.…”
mentioning
confidence: 99%
“…16 The proinflammatory cytokine macrophage migration inhibitory factor (MIF) is associated with inflammatory nephritis, 17,18 kidney transplant rejection, 19 and chronic kidney dysfunction. 20 Recently, Payen et al 21 reported that MIF is increased in septic patients who developed AKI within 48 hours after intensive care unit admission. Elevated concentrations of MIF induce leukocyte chemotaxis and tissue infiltration by leukocytes, 22,23 and this is followed by histopathological organ damage to the lungs 24 and kidneys, 25 among others.…”
mentioning
confidence: 99%
“…Macrophage migration inhibition factor is a proinflammatory cytokine which is involved in atherosclerosis and chronic kidney disease (8, 9). Until recently, there have not been many studies describing the role of MIF in kidney disease.…”
Section: Discussionmentioning
confidence: 99%
“…Until recently, there have not been many studies describing the role of MIF in kidney disease. A recent study showed that it was increased in the serum of patients with chronic kidney disease (9). In addition, it has been shown to be involved in kidney disease mediated by immunologic injury (8).…”
Section: Discussionmentioning
confidence: 99%